Leukocyte telomere dynamic change in patients with mild to moderate COVID-19 during three weeks of follow-up: relation with therapy: Running title: Leukocyte telomere length and COVID-19 - Kotur-Stevuljević, Jelena; Roksandić Milenković, Marina; Vekić, Jelena; Dimić, Nemanja; Dimić, Dejan; Ćujić, Danica; Guzonjić, Azra; Gnjatović, Marija; Todorović, Aleksandra; Bogavac-Stanojević, Nataša (Journal of Medical Biochemistry, 2025)
Summary Background: A three-year COVID-19 pandemic revealed a spectrum of disease severity and clinical manifestations. The most intriguing part of this phenomenon lays in inter-individual variability in COVID-19 course among patients, which is attributable to patient’s age, comorbidities and general health status. Focus of this follow-up study was to assess leukocyte telomere length change in mild-to-moderate COVID-19 patients and concomitant influence of inflammation, oxidative stress (OS), pulmonary involvement and implemented therapy on the course of the disease. Methods: Routine biochemical/haematological parameters, markers of OS (prooxidants and antioxidants), vitamin D, IgM and IgG antibodies level and relative length of leukocyte telomeres (rLTL) were measured at three time-points (at diagnosis, after 14 and 21 days from the disease onset) in blood samples of 31 consecutive COVID-19 patients, with a mild (n=16) and moderate (n=15) form of the disease, treated on an outpatient basis. Results: Although the patients had reduced rLTL at baseline (median: 0.592; 25th – 75th percentiles: 0.518-0.724), it significantly increased during the follow-up (median: 0.773; 25th – 75th percentiles: 0.615-0.923; P<0.01). The rate of telomere attrition was associated with the extent of OS and pulmonary involvement. During follow-up, the burden of OS was reduced, while antioxidant defence mechanisms were recovered. The use of antibiotics and N-acetylcysteine-propolis supplementation was associated with telomere lengthening. Conclusions: Results of this study revealed significant interaction between OS, inflammation and leukocyte telomere length attrition in COVID-19. Our data suggest that rRTL can be a biomarker that enables more precise therapy decision and accurate patient status estimation.